Mechanics of composite structures - Kollar, Laszlo Peter (Cambridge University Press, 2002)
An increase in the use of composite materials in areas of engineering has led to a greater demand for engineers versed in the design of structures made from such materials. Few existing books demonstrate advanced concepts or emphasize structures. This book addresses that need by offering students and engineers tools for designing practical composite structures. Among the topics of interest to the designer are stress-strain relationships for a wide range of anisotropic materials; bending, buckling, and vibration of plates; bending, torsion, buckling, and vibration of solid as well as thin walled beams; shells; hygrothermal stresses and strains; finite element formulation; and failure criteria. More than 300 illustrations, 50 fully worked problems, and material properties data sets are included. Some knowledge of composites, differential equations, and matrix algebra is helpful but not necessary, as the book is self-contained. Graduate students, researchers, and practitioners will value it for both theory and application.